New insights on the paleogeographic distribution of the Late Pleistocene ground sloth genus Xibalbaonyx along the Mesoamerican Corridor - Stinnesbeck, Sarah; Frey, Eberhard; Stinnesbeck, Wolfgang (Journal of South American earth sciences, 2018)
Here we describe the skull of a new species of Megaloychidae (Xenarthra) Xibalbaonyx microcaninus from the federal state of Jalisco in west-central Mexico based on a complete skull exhibited in the Museo Regional de Guadalajara (MRG). The specimen was originally collected in the Upper Pleistocene sediment of the Zacoalco paleolake (Jalisco) and is here assigned to the recently established genus Xibalbaonyx from the Late Pleistocene of Quintana Roo in south-eastern Mexico. The genus Xibalbaonyx thus had a wider geographic distribution than previously considered and ranges from central to southern Mexico.